Counseling about the Prevention and Handling of Sexual Violence in College - Triwanto, Triwanto; Aryani, Esti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The purpose of this legal counseling is to provide understanding to students about the prevention and handling of sexual violence in the tertiary environment. This needs to be done considering that sexual violence in the university environment is a real phenomenon that occurs. Among the students themselves still do not understand the concept of sexual violence Legal Counseling Activities to Faculty of Law Students, Universitas Slamet Riyadi (UNISRI) Surakarta is carried out online (online) using the Microsoft Team application. Counseling is given using the lecture method and interactive dialogue.